Volunteer economies : the politics & ethics of voluntary labour in Africa - Prince, Ruth Jane; Brown, Hannah (African issues., 2016)
Across Africa today, as development activities animate novel forms of governance, new social actors are emerging, among them the volunteer. Yet, where work and resources are limited, volunteer practices have repercussions that raise contentious ethical issues. What has been the real impact of volunteers economically, politically and in society? The interdisciplinary experts in this collection examine the practices of volunteers -- both international and local -- and ideologies of volunteerism. They show the significance of volunteerism to processes of social and economic transformation, and political projects of national development and citizenship, as well as to individual aspirations in African societies. These case studies -- from South Africa, Lesotho, Kenya, Tanzania, Zambia, Sierra Leone and Malawi -- examine everyday experiences of volunteerism and trajectories of voluntary work, trace its broader historical, political and economic implications, and situate African experiences of voluntary labour within global exchanges and networks of resources, ideas and political technologies. Offering insights into changing configurations of work, citizenship, development and social mobility, the authors offer new perspectives on the relations between labour, identity and social value in Africa.